How do you differentiate ${x^{\ln x}}$?
Answer
Verified
438k+ views
Hint: First express the given function in the form of $y = f\left( x \right)$. Then take logarithm on both sides of the equation to simplify it so as to make differentiation easier. Then differentiate both sides with respect to $x$ and make the substitution wherever required. Apply the chain rule of differentiation which is $\dfrac{{dy}}{{dx}} = \dfrac{{dy}}{{dt}} \times \dfrac{{dt}}{{dx}}$ to differentiate the composite functions.
Complete step by step answer:
According to the question, we have to show how to differentiate the function ${x^{\ln x}}$.
Let this function be denoted as $y$. Then we have:
$ \Rightarrow y = {x^{\ln x}}{\text{ }}.....{\text{(1)}}$
If we take natural logarithm on both sides, we’ll get:
\[ \Rightarrow \ln y = \ln {x^{\ln x}}\]
We know the logarithmic formula $\ln {a^b} = b\ln a$. On applying this formula, we have:
\[ \Rightarrow \ln y = \ln x\ln x\]
This can be written as:
\[ \Rightarrow \ln y = {\left( {\ln x} \right)^2}\]
Now if we put $\ln x = t$, we’ll get:
\[ \Rightarrow \ln y = {t^2}\]
Differentiating this equation both sides with respect to $x$, we’ll get:
\[ \Rightarrow \dfrac{d}{{dx}}\left( {\ln y} \right) = \dfrac{d}{{dx}}\left( {{t^2}} \right)\]
We know the chain rule of differentiation as shown below:
$ \Rightarrow \dfrac{{dy}}{{dx}} = \dfrac{{dy}}{{dt}} \times \dfrac{{dt}}{{dx}}$
Applying this rule for our function, we’ll get:
\[ \Rightarrow \dfrac{d}{{dx}}\left( {\ln y} \right) = \dfrac{d}{{dt}}\left( {{t^2}} \right)\dfrac{{dt}}{{dx}}\]
We know the formulas of differentiation $\dfrac{d}{{dx}}\ln x = \dfrac{1}{x}$ and $\dfrac{d}{{dx}}{x^2} = 2x$. Applying them, we’ll get:
\[ \Rightarrow \dfrac{1}{y}\dfrac{{dy}}{{dx}} = 2t\dfrac{{dt}}{{dx}}\]
Putting back the value of $t$, we’ll get:
\[ \Rightarrow \dfrac{1}{y}\dfrac{{dy}}{{dx}} = 2\ln x\dfrac{d}{{dx}}\left( {\ln x} \right)\]
Again applying the formula of differentiation, we’ll get:
\[
\Rightarrow \dfrac{1}{y}\dfrac{{dy}}{{dx}} = 2\ln x \times \dfrac{1}{x} \\
\Rightarrow \dfrac{{dy}}{{dx}} = \dfrac{{2y\ln x}}{x} \\
\]
Putting back the value of $y$ from equation (1), we’ll get:
\[ \Rightarrow \dfrac{d}{{dx}}\left( {{x^{\ln x}}} \right) = \dfrac{{2{x^{\ln x}}\ln x}}{x}\]
This is the required differentiation.
Note: Whenever we have to differentiate a composite function, we always use chain rule of differentiation after substitution. This makes a complex looking function simple from where we can differentiate step by step. For example, consider the given composite function:
$ \Rightarrow y = f\left( {g\left( x \right)} \right)$
To differentiate this function, we’ll substitute $g\left( x \right) = t$, we will have:
$ \Rightarrow y = f\left( t \right)$
Now we can apply chain rule of differentiation as shown below:
$ \Rightarrow \dfrac{{dy}}{{dx}} = \dfrac{d}{{dx}}f\left( t \right) \times \dfrac{{dt}}{{dx}}$
Now this differentiation is simple and we can do it step by step. After doing this, we can put back the value of $t$ to get the answer.
Complete step by step answer:
According to the question, we have to show how to differentiate the function ${x^{\ln x}}$.
Let this function be denoted as $y$. Then we have:
$ \Rightarrow y = {x^{\ln x}}{\text{ }}.....{\text{(1)}}$
If we take natural logarithm on both sides, we’ll get:
\[ \Rightarrow \ln y = \ln {x^{\ln x}}\]
We know the logarithmic formula $\ln {a^b} = b\ln a$. On applying this formula, we have:
\[ \Rightarrow \ln y = \ln x\ln x\]
This can be written as:
\[ \Rightarrow \ln y = {\left( {\ln x} \right)^2}\]
Now if we put $\ln x = t$, we’ll get:
\[ \Rightarrow \ln y = {t^2}\]
Differentiating this equation both sides with respect to $x$, we’ll get:
\[ \Rightarrow \dfrac{d}{{dx}}\left( {\ln y} \right) = \dfrac{d}{{dx}}\left( {{t^2}} \right)\]
We know the chain rule of differentiation as shown below:
$ \Rightarrow \dfrac{{dy}}{{dx}} = \dfrac{{dy}}{{dt}} \times \dfrac{{dt}}{{dx}}$
Applying this rule for our function, we’ll get:
\[ \Rightarrow \dfrac{d}{{dx}}\left( {\ln y} \right) = \dfrac{d}{{dt}}\left( {{t^2}} \right)\dfrac{{dt}}{{dx}}\]
We know the formulas of differentiation $\dfrac{d}{{dx}}\ln x = \dfrac{1}{x}$ and $\dfrac{d}{{dx}}{x^2} = 2x$. Applying them, we’ll get:
\[ \Rightarrow \dfrac{1}{y}\dfrac{{dy}}{{dx}} = 2t\dfrac{{dt}}{{dx}}\]
Putting back the value of $t$, we’ll get:
\[ \Rightarrow \dfrac{1}{y}\dfrac{{dy}}{{dx}} = 2\ln x\dfrac{d}{{dx}}\left( {\ln x} \right)\]
Again applying the formula of differentiation, we’ll get:
\[
\Rightarrow \dfrac{1}{y}\dfrac{{dy}}{{dx}} = 2\ln x \times \dfrac{1}{x} \\
\Rightarrow \dfrac{{dy}}{{dx}} = \dfrac{{2y\ln x}}{x} \\
\]
Putting back the value of $y$ from equation (1), we’ll get:
\[ \Rightarrow \dfrac{d}{{dx}}\left( {{x^{\ln x}}} \right) = \dfrac{{2{x^{\ln x}}\ln x}}{x}\]
This is the required differentiation.
Note: Whenever we have to differentiate a composite function, we always use chain rule of differentiation after substitution. This makes a complex looking function simple from where we can differentiate step by step. For example, consider the given composite function:
$ \Rightarrow y = f\left( {g\left( x \right)} \right)$
To differentiate this function, we’ll substitute $g\left( x \right) = t$, we will have:
$ \Rightarrow y = f\left( t \right)$
Now we can apply chain rule of differentiation as shown below:
$ \Rightarrow \dfrac{{dy}}{{dx}} = \dfrac{d}{{dx}}f\left( t \right) \times \dfrac{{dt}}{{dx}}$
Now this differentiation is simple and we can do it step by step. After doing this, we can put back the value of $t$ to get the answer.
Recently Updated Pages
Master Class 11 English: Engaging Questions & Answers for Success
Master Class 11 Computer Science: Engaging Questions & Answers for Success
Master Class 11 Maths: Engaging Questions & Answers for Success
Master Class 11 Social Science: Engaging Questions & Answers for Success
Master Class 11 Economics: Engaging Questions & Answers for Success
Master Class 11 Business Studies: Engaging Questions & Answers for Success
Trending doubts
10 examples of friction in our daily life
What problem did Carter face when he reached the mummy class 11 english CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
State and prove Bernoullis theorem class 11 physics CBSE
Proton was discovered by A Thomson B Rutherford C Chadwick class 11 chemistry CBSE
Petromyzon belongs to class A Osteichthyes B Chondrichthyes class 11 biology CBSE